(3ehdO Cejf CafOj GdLfOjs - (3GdLfOj, Cejf Hf NGdO Hf eMeO, J(B1257(3g`s ((3ESeGYjd Hf eMeO GdTGTs)
(3ChdgG (B:s
(3CHOC HSe Gddg aj ebGdj (B*** (3hCMeO Gddg Ydi GdJhGdj , acd ef jHOC HSe Gddg (B*** (3jfGd JjSjQG HdG GTJHGgs
(3BNQgG (B:s
(3hBdg hUMHg GdcQGe (B*** (3hGdMeO ddg Ydi GdJeGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 16s
(3eYLe GdeDdajf(B: 1 / 399s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs